Emotional Intelligence, Job Satisfaction. The Mediating Role of Interactional Justice - Mazellisya, Risca; Trinanda, Okki (Universitas Negeri Padang, 2024)
This study analyzes: (1) the effect of emotional intelligence on job satisfaction in the State Civil Apparatus (ASN) Office of the Ministry of Religion of Padang City (2) the effect of emotional intelligence on interactional justice in (ASN) Office of the Ministry of Religion of Padang City (3) the effect of interactional justice on job satisfaction (ASN) Office of the Ministry of Religion of Padang City (4) the effect of emotional intelligence on job satisfaction in employees of the Office of the Ministry of Religion of Padang City through interactional justice as a mediating variable. This research is quantitative research. The research sample was 61 employees of the Padang City Ministry of Religious Affairs Office. The sampling technique in this study was total sampling. Data collection is a questionnaire with a Likert scale. The results in this study indicate that (1) There is a significant and positive influence between Emotional Intelligence and Job Satisfaction in the State Civil Apparatus (ASN) of the Padang City Ministry of Religion Office, with a form of Job Satisfaction. (2) There is a significant and positive influence between Emotional Intelligence and Interactional Justice on the State Civil Apparatus (ASN) of the Padang City Ministry of Religious Affairs Office, (3) There is a significant and positive influence between Interactional Justice and Job Satisfaction on the State Civil Apparatus (ASN) of the Padang City Ministry of Religious Affairs Office (4) There is an indirect effect between the influence of Emotional Intelligence and Job Satisfaction.